Systematics of Willowsia jacobsoni (Börner, 1913) (Collembola, Entomobryidae): morphology, postembryonic development, distribution, mitogenome and phylogeny - Cipola, Nikolas Gioia; Katz, Aron D.; Bu, Yun; Godeiro, Nerivania Nunes (Zootaxa, 2025)
Willowsia jacobsoni (Börner, 1913) occurs in the Pantropical region, yet its evolutionary history and origin is poorly understood. Herein, morphological, molecular, and distributional data are used to evaluate the systematics of W. jacobsoni, providing novel descriptions and comparisons of its postembryonic development, a multi-locus molecular phylogeny for the Entomobryinae, and the first mitochondrial genome sequence for this species. Developmental stages of dorsal chaetotaxy are compared with other species of the genus and the head development is presented for the first time to Willowsia, including a new interpretation of primary and secondary chaetae. Bayesian and maximum likelihood analyses based on three genes (COI, 16S and 28S) were used to infer phylogenetic relationships for 35 Entomobryinae taxa, including 11 species of Willowsia. While the phylogenetic placement of W. jacobsoni was inconclusive, relationships of other Entomobryinae species were recovered with high support for the first time, including some that rendered Willowsia polyphyletic, corroborating with previous studies. We also characterized the mitogenome of a representative from the Chinese population of W. jacobsoni, which is the second one from this genus to be published. The species is recorded here for the first time in Brazil and Singapore, in addition to being the first record of the genus in Brazil. Considering that the genus has a great diversity in Asia, including several records of W. jacobsoni, this species was possibly introduced in America, or even in Africa. This comprehensive study of W. jacobsoni sheds light on the complexities surrounding its systematics, postembryonic development, and phylogenetic relationships among members of scaled and unscaled Entomobryinae.